FROM LINEAR TO CIRCULAR: Understanding the Construction Sector’s Transition in Madeira - Duarte de Almeida, I.; M.J. Delgado (ARQUIPÉLAGOS EM DIALOGO, 2026)
The construction sector is among the most resource-intensive industries, generating significant environmental impacts through its predominantly linear production model. Circular Economy (CE) principles offer a sustainable alternative by optimising resource use, reducing waste, and extending material lifecycles. This study examines the application of CE in the construction sector of the Autonomous Region of Madeira (RAM), focusing on decision-makers’ knowledge and perceptions, and identifying barriers, enablers, and current practices. A mixed-methods approach was adopted, combining a quantitative survey with qualitative semi- structured interviews. Findings reveal that, while the relevance of CE is widely acknowledged, practical implementation in RAM remains limited. Key barriers include a lack of knowledge and weak regulatory support, whereas financial incentives and improved material recovery are seen as critical enablers. Emerging strategies, such as modular construction and material reuse, suggest early signs of transition. Despite increased interest, broader adoption will require stronger policy commitment, industry engagement, and further research. The study contributes to ongoing debates on CE in construction and informs future regional strategies.